أثر الوثيقة الوقفية في الحفاظ على الدور التنموي للأوقاف - السدحان، عبدالله بن ناصر بن عبدالله (جامعة الملك عبدالعزيز - معهد الاقتصاد الإسلامي, 2018)
تستعرض هذه الورقة أحد الأدوات المهمة في الحفاظ على الدور التنموي للأوقاف، بإتقان صياغة الوثيقة الوقفية التي تعد بمثابة لائحة تشريعية للوقف، كما أنها بمثابة البوصلة التي تحدد مسار الوقف واتجاهه لعقود قادمة. كما تتناول الورقة الإشكالية القائمة حالياً في الكثير من الوثائق الوقفية، وهي كتابتها بشكل فردي من قبل الواقف بفكره الفردي ونظرته التي قد تكون محدودة زماناً ومكاناً، ومن هنا فكلما أحكمنا صياغة الوثيقة الوقفية وضبط أركانها الأساسية، استطعنا أن نحفظ الوقف من عوادي الدهر، وظلم بعض التشريعات، وفساد بعض النظار، أو ممارسات بعض موظفي الأوقاف الجائرة. ولا يمكن أن يتحقق ذلك إلا من خلال فكر جماعي متعدد التخصصات، وذلك عبر مكاتب أهلية أو خيرية مستقلة ذات خبرة: شرعية، وإدارية، وقانونية واجتماعية، واقتصادية، ولها رؤية استشرافية للمستقبل. إن هذا الأمر يمثل مطلبا إصلاحياً من داخل الكيان الوقفي لاستعادة الدور التنموي للأوقاف، يسير جنباً إلى جنب مع مطالبة الدول بالتشريعات الحامية، والمطمئنة للواقفين.
One of the most critical factors in preserving the developmental role of Awqaf is presented in this paper. The waqf declaration or document, is considered the governing bylaw which guides the present and future track of waqf for years to com. The waqf declaration needs to be articulated and written in a very robust and clear language. This paper shows some pitfalls in waqf declarations, which are usually phrased and dictated by the " Waqif (waqf’s donor)" as an individual, with short sighting for future needs. The importance of phrasing and broadening the language of the declaration to make it robust against mishandling, or misinterpretation by internal or external bodies. Careful articulation of all phrases in the waqf declaration requires clear identification of the "substance of waqf", the structure of its trustees, beneficiaries, spending policies, and investments strategies. A well written waqf declaration, can only be achieved by collective efforts of experts in multidiscipline and interrelated fields like Shari’ah, management, legal, social, investment, and futuristic planners. Corrective measures from within the Waqf bodies to enhance waqf declaration is needed to regain the developmental role of waqf, along with other efforts from authorities and waqf regulating bodies.
Keywords: الأوقاف -- الوثيقة الوقفية -- النظارة الجماعية -- مصارف الوقف -- استثمار الوقف